2008
DOI: 10.1007/s10815-008-9253-y
|View full text |Cite
|
Sign up to set email alerts
|

Low grade inflammation, as evidenced by basal high sensitivity CRP, is not correlated to outcome measures in IVF

Abstract: Purpose To assess the relationship between low-grade inflammation, measured as basal high sensitivity (hs)-CRP, and IVF outcome. Methods We recruited a total of 220 women undergoing infertility work up prior to IVF. Patients were selected for a BMI<30 kg/m 2 with an upper age limit of 40 years. Serum hs-CRP levels were measured on day 3 of a spontaneous menstrual cycle preceding ovarian stimulation. A sensitive two-site ELISA was used for analysis. Dose of gonadotrophins required, follicles days 8 and 10, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
17
4
Order By: Relevance
“…In contrast, other two papers found no relationship between CRP levels and IVF outcome (Almagor et al 2004;Orvieto et al 2004). Th e articles about hs CRP levels in IVF cycles showed no relationship (Robinson et al 2008;Seckin et al 2012). We found no diff erence in terms of hs CRP levels and there was no change during early post-IUI period.…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast, other two papers found no relationship between CRP levels and IVF outcome (Almagor et al 2004;Orvieto et al 2004). Th e articles about hs CRP levels in IVF cycles showed no relationship (Robinson et al 2008;Seckin et al 2012). We found no diff erence in terms of hs CRP levels and there was no change during early post-IUI period.…”
Section: Discussioncontrasting
confidence: 62%
“…There are a lot of studies in the literature researching a relationship between PCOS and inflammatory markers. While some investigators demonstrated significant elevations in NC, WBC count, or hs-CRP [11,29], others could not find increased inflammatory markers in PCOS patients undergoing IVF [30][31][32]. In our study, we demonstrated a significant difference between PCOS and control group regarding NC, neutrophil/leukocyte ratio, and also hs-CRP levels.…”
Section: Discussioncontrasting
confidence: 54%
“…Sarah Robinson et al in a preliminary study on correlation of baseline hs-CRP and in vitro fertilization (IVF) outcome had reported that, baseline hs-CRP is of no use as predictive marker of IVF outcome in routine clinical practice. Their study was conducted in non PCOS women 17.…”
mentioning
confidence: 99%